Comparison of the effectiveness of levonorgestrel intrauterine system and dienogest in the management of adenomyosis: A systematic review and meta-analysis - Akhigbe, R.E.; Afolabi, O.A.; Adegbola, C.A.; Akhigbe, T.M.; Oyedokun, P.A.; Afolabi, O.A. (European journal of obstetrics & gynecology and reproductive biology, 2024)
•Dienogest led to a significant reduction in visual analogue scale score compared with the levonorgestrel intrauterine system (LNG-IUS).•Dienogest reduced uterine volume significantly compared with LNG-IUS.•The occurrence of side effects was comparable in the dienogest and LNG-IUS groups. Adenomyosis is a gynaecological lesion that impairs female fertility and contributes to reduced quality of life. There are several surgical and medical options for the management of this lesion; however, women who wish to conceive opt for medical therapies such as the levonorgestrel intrauterine device (LNG-IUS) and dienogest, which have various outcomes. To date, there is no consensus regarding which is more effective. To compare the effectiveness of LNG-IUS and dienogest for the management of adenomyosis, and explore the risk of occurrence of known side effects for both treatments. Design: Systematic review and meta-analysis exploring the effectiveness of LNG-IUS and dienogest for the management of adenomyosis. A literature search was conducted using PICO guidelines and EMBASE, PubMed/MEDLINE, Scopus and Web of Science databases. Only clinical trials were collected and analysed. Of the 792 studies that were initially identified, six were eligible for inclusion in this study. The studies included a total of 707 women; of these, 270 were treated with LNG-IUS, 354 were treated with dienogest, and 83 were controls. All the studies were from Asia (Bangladesh n = 1, China n = 2, India n = 1, Japan n = 1, South Korea n = 1). Dienogest was found to reduce pelvic pain significantly, evidenced by a lower visual analogue scale score, compared with LNG-IUS. Also, dienogest led to a significant reduction in uterine volume compared with LNG-IUS. However, subjects in the LNG-IUS group had significantly higher levels of haemoglobin than those in the dienogest group. Nonetheless, the occurrence of side effects such as weight gain, breast tenderness/distension, headache, insomnia/sleep disorder, depression/mood disorder, skin disorder/acne, and coital discomfort/reduced libido were comparable in both treatment groups. Dienogest may be more effective than LNG-IUS for the management of adenomyosis, as it shows a superior effect in the reduction of pelvic pain and uterine volume. As only six studies were included in the present meta-analysis due to the paucity of data in the literature, it is recommended that well-designed randomized controlled trials comparing the effectiveness of dienogest with LNG-IUS should be conducted.